Dimensi Teologi dalam Ritual Sedekah Bumi Masyarakat Made - Nugroho, Hassan (Fakultas Ushuluddin, Adab dan Humaniora Institut Agama Islam Negeri (IAIN) Jember, 2018)
This study discusses the phenomenon of tradisi sedekah bumi (giving alms to the mother Earth) in the Village of Made, Sambikerep, Surabaya. The tradition of giving alms to the mother Earth –which has been commonly performed by agrarian society (rural people) in Java as a manifestation of thankfulness upon